Mining electric vehicle adoption of users - Rodrigues, Rui (2021)
Rodrigues, R., Albuquerque, V., Ferreira, J. C., Dias, M. S., & Martins, A. L. (2021). Mining electric vehicle adoption of users. World Electric Vehicle Journal, 12(4), 1-31. [233]. https://doi.org/10.3390/wevj12040233 ------------------------------------------------------------------------------------- Funding Information: Funding: This research was funded by the Foundation for Science and Technology (FCT) through ISTAR-IUL’s project UIDB/04466/2020 and UIDP/04466/2020. Funding Information: Acknowledgments: J.C.F. received support from the Portuguese National Funds through FITEC— Programa Interface, with reference CIT INOV—INESC INOVAÇÃO—Financiamento Base. Publisher Copyright: © 2021 by the authors. Licensee MDPI, Basel, Switzerland.